Evaluation of familial aggregation, vegetable consumption, legumes consumption, and physical activity onfunctional constipation in families of children with functional constipation versus children without constipation - Dehghani, Seyed Mohsen; Moravej, Hossein; Rajaei, Elahe; Javaherizadeh, Hazhir (Gastroenterology Review/Przegląd Gastroenterologiczny, 2015)
Introduction: Constipation is a frequent complication in paediatrics. Most of the constipation is functional. Functional constipation constitutes 25% of visits in paediatric gastroenterology clinics. Two studies were published regarding aggregation or clustering of functional constipation. Only one of these research projects was about a paediatric population. Aim: To elucidate the cluster pattern of constipation among the families of children with constipation. Material and methods : This case-control study was carried out on the families of 37 children < 18 years old with chronic functional constipation and the families of 37 healthy children as controls. Cases were enrolled in the study according to Rome III criteria for constipation. The control group was selected from children < 18 years old who visited the well baby clinic of the university. Parents and siblings were evaluated regarding constipation. Rome II and III were used for evaluation of constipation for adults and children, respectively. Data was analysed using SPSS (Chicago, IL, USA). The 2 and t-test were used for comparison. Results : Physical activity and vegetable consumption were seen more frequently in the control group compared to the cases, but these differences were statistically insignificant. Constipation in mothers was significantly higher in the case group compared to the control group (p = 0.015). There was no significant difference between the two groups regarding exercise and vegetable consumption. Conclusions : The frequency of constipation among mothers was significantly higher in the case group compared to the control group. Another study is recommended in a larger population for evaluation of genetic background, diet, physical activity, and familial clustering among mothers of children with constipation.